Targeting HER2 beyond breast cancer - Bhatnagar, Sanchita (Mol Cell Oncol, 2019)
The structural basis of blocking human epidermal growth factor receptor-2 (HER2) dimerization remains of great interest to generate effective anti-cancer therapies. Despite clinically feasible outcome in mammary tumors, a fine consensus between efficacy and safety remains a critical challenge beyond breast cancer. Here we extrapolate on the balancing act using recently reported clinical findings in salivary ductal carcinomas.